Simulation of the Load Sharing for the Four Gears Parallel Drive of Shield Machine Cutter - Wang Lihua; Zhang Chunyou; Wu Xiaoqiang (Jixie chuandong, 2015)
The dynamics equation of the four gears parallel drive system of shield machine cutter is established.The 3D model of the four gears parallel drive system is established by using the UG software.The dynamic process of the four gears parallel drive system is simulated by using the ADAMS software.Then the influence of meshing damping,meshing stiffness,backlash and distribution of driving gear on the load sharing are also analyzed.The research shows that the larger the difference between meshing stiffness and meshing damping is,the more uneven the load sharing is,when the driving load changes,backlash has a larger effect on the load balance,the different distributions of driving gear have rather a great impact on the stability of driven system.The results can provide theoretical basis for the design and manufacture of the four gears parallel drive system.